2015
DOI: 10.1186/s12936-015-0948-0
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of the efficacy of artesunate and three quinine regimens in the treatment of severe malaria in children at the Ebolowa Regional Hospital, Cameroon

Abstract: BackgroundSevere malaria is a medical emergency with high mortality in children below 5 years of age especially in sub-Saharan Africa. Recently, quinine has been replaced by artesunate as the first-line drug in the treatment of severe malaria in Cameroon. No local data are yet available on the efficacy of artesunate with respect to the different quinine regimens used in this setting. This study was undertaken at the Ebolowa Regional Hospital (ERH), which is located in a region of perennial transmission of mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The results of the clinical effectiveness of each treatment group measured in PRR 24 , is presented in Table 1 and have been previously reported in another publication [15]. Results show that ARTES had statistically significantly higher effectiveness than any of the quinine treatment alternatives.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The results of the clinical effectiveness of each treatment group measured in PRR 24 , is presented in Table 1 and have been previously reported in another publication [15]. Results show that ARTES had statistically significantly higher effectiveness than any of the quinine treatment alternatives.…”
Section: Resultssupporting
confidence: 55%
“…Economic data was collected alongside clinical effectiveness data from each patient using a questionnaire administered by trained researchers. The result of the comparative effectiveness of the treatment alternatives has been previously reported and published [15]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies concluded to the continuous efficacy of artemisinin base combination in Cameroon [128, 129, 131]. For diagnostic and treatment of malaria cases, several programmes have been conducted across the country in order to strengthen health care workers practices [132134]. Additional case management programmes conducted include seasonal malaria chemoprevention in the North and Far-North regions.…”
Section: Malaria Treatment and Case Managementmentioning
confidence: 99%
“…Hypersensitivity drug reactions (HDRs) are, in contrast to most other adverse drug reactions, mediated by specific immunological pathways and are considered largely independent of the administered dose or pharmacological action [27]. Cases of allergic reaction following treatment with artemisinin derivatives have consistently been reported since the first clinical trials systematically evaluating artemisinins [5,19,[28][29][30][31][32][33][34][35].…”
Section: Adverse Events and Tolerability Of Artemisininmentioning
confidence: 99%